Analisis Penerapan Metode Scrum Pada Pengembangan Sistem Informasi Akuntansi Koperasi - Rizaldi, Alexander; Maria, Evi; Wahyono, Teguh; Purwanto, Purwanto; Hartomo, Kristoko Dwi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Koperasi are one of the drivers of the economy in Indonesia. But in the operations of the koperasi, there are many problems such as lack of information, unrecorded deposits, the amount of credit that exceeds capacity, and lack of accuracy in accounting calculations. The study used the object of the employee koperasi of SWCU (Satya Wacana Christian University) Salatiga by conducting an observation process on the ongoing koperasi business system. The design of a koperasi accounting information system using a web platform with the basic model of the Scrum Process. The Scrum process model is a software development management framework with iterative and incremental characteristics and properties. The koperasi accounting information system that is built based on Scrum can reduce previous processing errors and can increase the speed and accuracy of data processing so that in the short term it can improve koperasi performance. System performance is tested by black box testing method to ensure all features can work properly. The test results showed that the system built can help reducing problems occurred in the operational process of koperasi, particularly in the accounting process. The results show that the system is more efficient to reduce problems occurred in the operational process of koperasi, reduce time in transaction processing, increase accuracy in the accounting process, and make it easier for users to produce reports with high validity.